Development of video-based floor gymnastics learning media to improve the understanding of the concept of sman 8 cirebon students - Saputra, Aim Suka; Suganda, Mikkey Anggara (Jurnal Ilmu Keolahragaan, 2024)
This study aims to determine the influence of the use of video-based learning media on the understanding of the concept of Physical Education, Sports, and Health (PJOK) of high school grade XI students. The main focus of the study was on simple movement skills in floor gymnastics activities. The research method used was quasi-experimental with a pretest-posttest control group design. The research subjects consisted of two groups, namely a small-scale class (XI MIPA 5) and a large-scale class (XI MIPA 3) at SMA Negeri 8 Cirebon. The research instrument used concept understanding tests before and after treatment (pretest and posttest). The results of the data analysis showed that there was a significant increase in the understanding of the concept of PJOK after the use of learning video media, especially in large-scale classrooms. Statistical tests show that the data is distributed normally and homogeneously. The average posttest score of large-scale classes is higher than that of small-scale classes. The t-test showed that the significance value was less than 0.05, which means there was a significant difference between the two groups. The conclusion of this study is that the use of video-based learning media is effective in increasing students' understanding of PJOK concepts, especially in floor gymnastics materials. Video media not only increases students' interest and engagement in learning, but also facilitates visual and practical understanding of movement.